2012
DOI: 10.1002/hep.24689
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional B-cell activation in cirrhosis resulting from hepatitis C infection associated with disappearance of CD27-Positive B-cell population

Abstract: Background Chronic hepatitis C virus infection is a leading cause of cirrhosis and hepatocellular carcinoma. Both advanced solid tumors and hepatitis C have previously been associated with memory B-cell dysfunction. In this study we sought to dissect the impact of viral infection, cirrhosis and liver cancer on memory B-cell frequency and function in the spectrum of HCV disease. Methods Peripheral blood from healthy donors, HCV-infected patients with F1–F2 liver fibrosis, HCV-infected patients with cirrhosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 46 publications
(57 reference statements)
9
85
1
4
Order By: Relevance
“…Among these explanations, activation-induced apoptosis has been contradicted by more recent data suggesting that B-cells in HCV-infected individuals are relatively resistant to apoptosis [11,12]. Rather than being expanded, we previously demonstrated that the circulating memory B-cell population disappears in cirrhotic but not non-cirrhotic HCV-infected patients [13]. The reduction in memory B-cells strongly correlated with multiple parameters of liver dysfunction and portal hypertension, also occurred in individuals with cirrhosis from other causes, and associated with a reduction in B-cell antigen-presenting cell function.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Among these explanations, activation-induced apoptosis has been contradicted by more recent data suggesting that B-cells in HCV-infected individuals are relatively resistant to apoptosis [11,12]. Rather than being expanded, we previously demonstrated that the circulating memory B-cell population disappears in cirrhotic but not non-cirrhotic HCV-infected patients [13]. The reduction in memory B-cells strongly correlated with multiple parameters of liver dysfunction and portal hypertension, also occurred in individuals with cirrhosis from other causes, and associated with a reduction in B-cell antigen-presenting cell function.…”
Section: Introductionmentioning
confidence: 79%
“…In our original cohort described in Doi et al [13], we described a collapse of the peripheral CD27 + B-cell subset associated with cirrhosis. In our expanded cohort (Fig.…”
Section: Cd27 − Cd21 − B-cells Are Relatively Overrepresented In B-cementioning
confidence: 97%
“…Depletion of B-cells, predominantly CD27 + -memory B-cells and hyporesponsiveness to TLR-activation has been observed in cirrhotic patients [38]. Also lymphopenia is commonly observed in cirrhosis and affects both T-helper and cytotoxic T cells, mainly affecting naive T cells [39,40].…”
Section: Infection Related Mortality In Acute-on-chronic Liver Failurementioning
confidence: 99%
“…Moreover, no study has made an exhaustive analysis of miRNA expression patterns from peripheral blood cells. As (i) circulating peripheral blood cells including monocytes and lymphocytes have been previously involved in liver fibrogenesis [133][134][135], and (ii) treatment response has been significantly correlated with the proportion and activation state of regulatory T cells [136,137] and T helper cells [138][139][140], there is a need for a more exhaustive analysis of the miRNAs expressed in these cells in vivo and a further characterization of the molecular pathways involved.…”
Section: Future Perspectivesmentioning
confidence: 99%